Analisis Keluhan Pelanggan Toserba Pusat Pondok Pesantren Sunan Drajat Dan Strategi Perbaikan Pelayanan - Hanny Lubaba; Leyla Ashifa P; Julia Firnanda W (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
This study aims to analyze the most dominant customer complaints, examine management responses, and formulate service improvement strategies at Toserba Pusat Pondok Pesantren Sunan Drajat Lamongan. The study employs a descriptive qualitative approach supported by simple quantitative data. Data were collected through questionnaires distributed to 100 respondents and interviews with management on each floor of the department store. Quantitative data were analyzed by calculating the mean and percentage values of several indicators, including service, product availability, price, and consumer preference. Meanwhile, qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that customer complaints vary across floors. On the first floor, complaints are mainly related to price clarity and cashier service speed. On the second floor, the dominant complaints concern product availability, particularly the out-of-stock condition of several electronic products. Meanwhile, on the third floor, complaints are associated with low customer preference, influenced by limited product variety and price perception. Management responses include routine evaluations, recording customer needs, and ordering products from suppliers. Service improvement strategies implemented include adding cashier units and price scanning machines, procuring products based on customer demand, and implementing product innovation and discount programs to increase customer satisfaction and loyalty.